PENGARUH INTERNET BANKING TERHADAP KEPUASAN NASABAH (STUDI KASUS PADA NASABAH BANK RAKYAT INDONESIA SYARIAH CABANG PALEMBANG) - Hartawan, Dedi (Islamic Economics Program, Faculty of Islamic Economics and Business, 2017)
This study aims to determine the effect of internet banking to customer satisfaction at BRI Syariah Branch Palembang. The population in this study are customers of Bank Rakyat Indonesia Syariah branch of Palembang. Based slovin method indicates that the sample in this study were as many as 80 customers. By way of sampling puposif (puposiv sampling) is the way research is done sampelyang choose subjects based on specific criteria set researcher. The results showed that the variables significantly influence the internet banking customer satisfaction BRI Syariah bank branch Palembang.